The Influence of Qana’ah (Contentment) and Gratitude towards Future Anxiety In Mahasantri (University Students Who Attend Pesantren/Islamic Boarding Institution) - Saifuddin, Ahmad; Nisa, Lia Faridatun (Gadjah Mada Journal of Psychology (GamaJoP), 2025)
Qana’ah (contentment) and gratitude are commendable virtues taught in mahasantri (university student who attend in pesantren/Islamic boarding institution). These virtues serve as invaluable assets to navigate through adversities related to apprehensions of future. Despite the cultivation of virtues among mahasantri, some still grapples with anxiety concerning future. Therefore, this research aimed to explain the influence of qana’ah (contentment) and gratitude toward future anxiety in mahasantri using quantitative method. Meanwhile, the participants of this study was 201 mahasantri in Raden Mas Said State Islamic University Surakarta which was obtained by cluster random sampling. The results showed that qana’ah (contentment) and gratitude simultaneously influence future anxiety. Separately, the two predictors also have negative influences on future anxiety. It is hoped that the research will be able to become a reference for teenagers to adopt qana’ah and gratitude. Apart from that, this research is also expected to be an important modality in developing qana’ah therapy to reduce future anxiety.